If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(3x + -10) = -24 Reorder the terms: 3x(-10 + 3x) = -24 (-10 * 3x + 3x * 3x) = -24 (-30x + 9x2) = -24 Solving -30x + 9x2 = -24 Solving for variable 'x'. Reorder the terms: 24 + -30x + 9x2 = -24 + 24 Combine like terms: -24 + 24 = 0 24 + -30x + 9x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(8 + -10x + 3x2) = 0 Factor a trinomial. 3((4 + -3x)(2 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {1.333333333, 2}
| cos(6x)-cos(2x)= | | x+30=40 | | 3x-8y+6y=8 | | (3x-5)(9x+1)=0 | | 2x^2=4(x-5) | | 12x^3+20x^2-8x=0 | | -5n(5n-7)=0 | | 12x^3+20x-8x=0 | | 6(4x-8)+8=24x-40 | | 0.33=ln | | 3x+1=3(x-8) | | 2y=-1.5x+38 | | a/9-=6 | | 12y^2-2=5y | | 3x^3-x^2+36X-12=0 | | 3(2)+7y=7 | | 66x+12=24 | | (3e^2x+4)=6 | | Log(Lnx)= | | (5+H)*2=36 | | 8y+4y=8 | | (5*H)*2=36 | | 8(x-4)+5=-27 | | (z^2-16)(z^2-49)=0 | | 24x+-36=18 | | 3x^2-x+36=0 | | 25b+10b^2= | | 2x^3-2x^2+18x=0 | | 5(2x+2)-2=10x+8 | | P+p+p=300 | | 9x+29=90 | | P/5=20 |